EXPLORING CULTURAL FRONTIERS: THE INTERPLAY OF METAFICTION AND TRANSLATION IN SELECTED ENGLISH FICTION - Vats, Nidhi; Goyal, Keshav (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research examines the complex interaction between metafiction and translation within English fiction. It illustrates how these literary devices aid narrative crafting and crucial cultural examinations. While translation is commonly viewed as a simple switch from one language to another, it functions as an impactful technique that fortifies narratives by crossing linguistic and cultural divides. Alternatively, metafiction serves as a structure that self-references its own constructed nature, provoking audiences to critically ponder the underlying operations and assumptions that underpin any narrative. This study analyzes the utilization of translation and metafiction in works such as English, August: An Indian Story by Upamanyu Chatterjee, and A House for Mr. Biswas by V.S. Naipaul to demonstrate how these writers question conventional narrative practices to profoundly explore the intricacies of identity development. Chatterjee in English, August: An Indian Story, employs translation as a formal device of fictional art which not only reflects the tension between vernacular languages and English but also contains metanarrative elements. These include, for example, among others the protagonist's disunited selfhood and narrative truth. In A House for Mr. Biswas, Naipaul likewise uses translation embedded within a work of fiction to highlight the cross-cultural nature of Indian traditions with those from the West; creating for us at least some lens on how hybrid and authentic discourses should be made. The paper also looks at the challenges inherent in translating metafiction into practice as maintaining cultural authenticity and accessibility of the narrative strategies. Critics have argued that metafiction and translation wipe out the real cultural essence while distancing readers; however, they are seen as a source of inspiration for further development and intercultural exchange.